DEVELOPMENT OF CATHOLIC RELIGIOUS LEARNING WITH THE PROJECT BASED LEARNING (PjBL) APPROACH - Mite, Agustina Dede; Eveline, Siregar; Robinson, Situmorang (Journal of Education Research and Evaluation, 2021)
The main purpose of this research is to develop Catholic Religion learning approach based -on project-based learning (PjBL) on the 7th Grade Junior High School Students of Saint Marie which is hoped can help teachers and students in the learning process as one of strategic learning to solve the problem teachers have faced which only focus on the result of cognitive aspect. The procedure in improving Catholic Religion uses developing MPI model with project-based learning (PjBL) on learning step design. Data collection technic is taken by observation, interview, and questionnaire. Data analysis technic which is used for this research is qualitative and quantitative. According to qualification analysis result from the resource expert for the attainment level is 95,4% with very good qualification and can be used without revision and according to qualification analysis result from design learning expert for the attainment level is 91,2% with very good qualification and can be used without revision too. Learning development by using project-based learning approach will be very effective to achieve learning objectives in affective aspect optimally. This result of this research implies that learning development by project-based learning is very useful in learning Catholic Religion especially in affective aspect. In conclusion, learning objective either cognitive and affective aspect can be achieved and every student personally will get the result of learning process well.Keywords: Project based learning, Catholic Religion learning, MPI model.